Design and integrated tension test of a large-scale modular CFRP wheel-spoke-shaped structure. (15th January 2023) - Li, Shiping; Zhang, Yibei; Mi, Xiang; Huang, Xiaohui; Chen, Wujun
Highlights: A new modular design scheme for large-scale modular CFRP wheel-spoke-shaped pre-tensioned structures is proposed. The design scheme of the CFRP wheel-spoke-shaped pre-tensioned structure is verified. A single-point synchronous graded tensioning method was proposed. The stiffening ring structure achieves a self-equilibrium at the designed prestress level. Abstract: The development of large-scale space flight platforms and space vehicles has led to the definition of ultra-lightweight and large-span structural design requirements for backbone structures. Taking the large-scale production, lightweight, modularization, and rapid assembly requirements as the optimization design goals, the modularization technology, connection method, and assembly mode of a carbon fiber reinforced polymer (CFRP) truss structure are studied; leading to the proposal of a new modular design scheme for large-scale modular CFRP wheel-spoke-shaped pre-tensioned structure. Based on the single-point synchronous graded tensioning method, an integrated tension test of the large-scale modular CFRP wheel-spoke-shaped structure is carried out with an integrated tension equipment. The consistency of the strain changed when the upper and lower radial cables was tested, the strain characteristics of the triangular joint frame and the CFRP truss during the push-tensioning process were analyzed, and the overall deformation of the large-scale modular CFRP wheel-spoke-shaped structure was studied. The proposed single-point synchronous graded tensioning method can simply and efficiently perform tensioning consistency in the prestressed cables, and therefore solve the engineering issues of low precision, complex tension application, and assembly difficulties in existing circular multi-point synchronous graded tensioning method. The large-scale modular CFRP wheel-spoke-shaped pre-tensioned structure achieves both structural weight reduction and large-scale structural design goals, while having broad application prospects in various aerospace vehicles and space structures. The proposed modular technology, wheel-spoke structure design scheme, and single-point synchronous graded tensioning method have high a scientific contribution, while providing technical support for the development of new spacecrafts.